2024
DOI: 10.1039/d3ee02459h
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of dry air and surfactants enables water to be a promising green solvent for stable and efficient perovskite solar cells

Yanrui Zhang,
Lixia Ren,
Peng Zhai
et al.

Abstract: In recent years, the perovskite has emerged as a prominent one to compete with all other existing PV materials. However, its fabrication typically involves the use of toxic organic solvents....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…PSCs fabricated from PbCO 3 NFs exhibited an average PCE of 23.64% under dry air conditions and showed excellent stability under continuous light exposure. Later, the team investigated the crystallization of Pb(NO 3 ) 2 at different RHs [333]. Moisture in ambient air played a key role in the rate of nucleation of Pb(NO 3 ) 2 (figure 25(c)).…”
Section: Eco-friendly Device Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…PSCs fabricated from PbCO 3 NFs exhibited an average PCE of 23.64% under dry air conditions and showed excellent stability under continuous light exposure. Later, the team investigated the crystallization of Pb(NO 3 ) 2 at different RHs [333]. Moisture in ambient air played a key role in the rate of nucleation of Pb(NO 3 ) 2 (figure 25(c)).…”
Section: Eco-friendly Device Processingmentioning
confidence: 99%
“…(c) Schematic of crystallization under different relative humidity. Reproduced from[333] with permission from the Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…On the other hand, water, as the most important protic solvent, directly impacts the stability of the FAPbI 3 perovskite precursor solution. At the same time, humidity (water) also plays complex and mysterious roles in preparing high-efficiency and long-term stable devices. This proves that water could affect the reliability and quality of large-scale industrial preparation of PSCs. Kerner et al reported that trace water is a benign impurity in the formation of MFAI .…”
Section: Introductionmentioning
confidence: 99%
“…The first study demonstrating the formation of a perovskite film using water for PSC devices with a PCE of 12.58% was reported in 2015 . Subsequent investigations have delved into the kinetic intricacies of crystal formation, leading to adjusted perovskite compositions that enhance the performance of PSCs with current record PCE of 24.14%, demonstrating the potential of water-based solution processing in PSC fabrication.…”
mentioning
confidence: 99%
“…(c) J – V curves of the champion PSCs made under low-humidity conditions and with different concentrations of potassium oleate additive. The figure is reproduced from ref . Copyright The Royal Society of Chemistry 2024.…”
mentioning
confidence: 99%